High P–T Raman study of transitions in relaxor multiferroic Pb(Fe0.5Nb0.5)O3. (2nd September 2015) - Wilfong, Brandon; Ahart, Muhtar; Gramsch, Stephen A.; Stock, Chris; Li, Xiaomin; Luo, H.; Hemley, Russell J.
Abstract : The vibrational and structural properties of Pb(Fe0.5 Nb0.5 )O3 have been investigated using Raman spectroscopy up to 40 GPa at 300 K and from 300 to 415 K at selected pressures. The measurements reveal three phase transitions, at 5.5, 8.7, and 24 GPa at room temperature. The temperature dependences of the spectra indicate transitions at 1.5 GPa, at 335 and 365 K. The results are consistent with the appearance of an intermediate tetragonal P 4mm phase between the ferroelectric R 3m and paraelectric P m‐3m phases. A P–T phase diagram is proposed that allows further insight into the magnetoelectric coupling present in this material. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The vibrational and structural properties of Pb(Fe0.5 Nb0.5 )O3 have been investigated using Raman spectroscopy up to 40 GPa at ambient temperature and from ambient to 415 K at selected pressures. Three phase transitions were noted via the pressure evolution at 5.5, 8.7, and 24 GPa at room temperature. The temperature dependences of the Raman spectra indicated two phase transitions at 1.5 GPa, at 335 and 365 K, which support the appearance of an intermediate tetragonal P 4mm phase between ferroelectric R 3m and paraelectric P m‐3m phases. At 2.5, 3.9, and 7.4 GPa, the system showed one phase transition with temperature evolution at 337, 348, and 332 K, respectively. A P–T phase diagram is proposed that allows further insight into the magnetoelectric coupling present in this material.